Critically ill adult patients with acute leukemia: a systematic review and meta-analysis - Dara Chean; David Luque-Paz; Daniele Poole; Sofiane Fodil; Etienne Lengliné; Thibault Dupont; Achille Kouatchet; Michael Darmon; Élie Azoulay (Annals of Intensive Care)
Abstract Background To describe the use of life-sustaining therapies and mortality in patients with acute leukemia admitted to the intensive care unit (ICU). Methods The PubMed database was searched from January 1st, 2000 to July 1st, 2023. All studies including adult critically ill patients with acute leukemia were included. Two reviewers independently selected the studies, assessed bias using the Newcastle-Ottawa scale for cohort studies, and performed data extraction from full-text reading. We performed a proportional meta-analysis using a random effects model. The primary outcome was all-cause ICU mortality. Secondary outcomes included reasons for ICU admission, use of organ support therapies (mechanical ventilation, vasopressors and renal replacement therapy), hospital, day-90 and one-year mortality rates. Results Of the 1,331 studies screened, 136 (24,861 patients) met the inclusion criteria and were included in the meta-analysis. Acute myeloid leukemia affected 16,269 (66%) patients, acute lymphoblastic leukemia affected 835 (3%) patients, and the type of leukemia was not specified in 7,757 (31%) patients. Acute respiratory failure (70%) and acute circulatory failure (25%) were the main reasons for ICU admission. Invasive mechanical ventilation, vasopressors and renal replacement therapy, were needed in 65%, 53%, and 23% of the patients, respectively. ICU mortality was available in 51 studies (6,668 patients, of whom 2,956 died throughout their ICU stay), resulting in a metanalytical proportion of 52% (95% CI [47%; 57%]; I 2 93%). In a meta-regression, variables that influenced ICU mortality included year of publication, and intubation rate. Conclusion Acute respiratory failure is the main reason for ICU admission in patients with acute leukemia. Mechanical ventilation is the first life-sustaining therapy to be used, and also a strong predictor of mortality. Trial registration This study’s protocol was preregistered on PROSPERO (CRD42023439630).